THE EFFECT OF SIMULATED COMMUNICATIVE APPROACH ON STUDENTS’ WRITING COMPETENCY OF THE SEVENTH GRADE STUDENT OF SMP WIDHYA BHUANA MUNGGU BASED ON TEXT TYPE - ., PANDE MADE PRADNYANA PUTRA; ., PROF. DR. DEWA KOMANG TANTRA, M.Sc.; ., PROF. DR. NI NYOMAN PADMADEWI, M.A. (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2016)
this research aimed at investigatingthe effect of simulated comunicative approach in students' writing competency based on text type. it was an experimental research which implemented posttest only control group design. the population was 128 students of four classes of seventh grade students of SMP Widhya Bhuana Munggu. those subject of the research were divided into two groups they were control group and experimental group.both of the groups were given diggerent treatments and they were ended by posttest. the result of the post test was analyzedusing spss statistic. the result shows that the experimental group is higher than control group. so it can be conclude that simulated communicative approach a significant effect on the students' writing competencyKata Kunci : writing competency, text type this research aimed at investigatingthe effect of simulated comunicative approach in students' writing competency based on text type. it was an experimental research which implemented posttest only control group design. the population was 128 students of four classes of seventh grade students of SMP Widhya Bhuana Munggu. those subject of the research were divided into two groups they were control group and experimental group.both of the groups were given diggerent treatments and they were ended by posttest. the result of the post test was analyzed using spss statistic. the result shows that the experimental group is higher than control group. so it can be conclude that simulated communicative approach a significant effect on the students' writing competencykeyword : writing competency, text type